Effect of Guava Extract Administration on Megakaryocytes Amount in Mice Femur - Nur Atik; Maqrizi D. S. Munawir; Susan Tarawifa; Hartati P. Darmadji (Indonesian Journal of Clinical Pharmacy, 2017)
Dengue fever is a disease spread by mosquito’s bite. Dengue fever is marked by the presence of thrombocytopenia. Traditional crops such as guava are commonly used to treat dengue fever. This research aims to know the effect of guava extract administration towards megakaryocytes amount in mice femur. The study was conducted at the Laboratory of Pharmacology and Therapy, Histology Laboratory of Faculty of Medicine at Universitas Padjadjaran, Eijkman, Bandung from September until November 2016 using laboratory experimental study design. 20 Swiss webster mice strains were divided randomly into 4 groups. Group I and II were administered quinine 2.8 mg/20 grBW/day for 14 days to decrease amount of trombocytes. Group II and III were administered guava extract 0.785 mg/20 grBW/day for 5 days. Group IV was administered aquadest for 19 days. In the 27th day, the mice left femurs were collected and made into paraffin section preparations with hematoxylin-eosin staining and then observed under microscope. Group IV had the most megakaryocytes followed by Group II, III, and I. Based on Kruskal-Wallis test, a significant difference was shown (p<0.05). Mann-Whitney test showed that there were significant differences between Group I and Group II, III, and IV. Meanwhile there was no significant difference between normal mice and extract-given mice. Guava extract is proven statistically significant to increase the megakaryocytes amount in thrombocytopenic mice without increasing number of megakaryocytes in normal mice.Keywords: Dengue fever, guava extract, megakaryocyte, quinine Efek Pemberian Ekstrak Jambu Biji terhadap Jumlah Megakariosit pada Femur MencitAbstrakDemam berdarah merupakan penyakit yang dapat disebarkan melalui gigitan nyamuk. Demam berdarah ini ditandai dengan adanya trombositopenia. Tanaman tradisional berupa jambu biji banyak digunakan untuk mengobati demam berdarah. Penelitian ini bertujuan untuk mengetahui efek pemberian ekstrak jambu biji terhadap jumlah megakariosit pada femur mencit. Penelitian ini dilakukan di Laboratorium Farmakologi dan Terapi, Laboratorium Histologi Universitas Padjadjaran, Eijkman, Bandung dari bulan September hingga November 2016. Sebanyak 20 ekor mencit galur Swiss webster dibagi menjadi 4 kelompok. Kelompok I dan II diberikan quinine 2,8 mg/20 grBB/hari per oral selama 14 hari agar mencit trombositopenia. Kelompok II dan III diberikan ekstrak jambu biji 0,785 mg/20 grBB/hari per oral selama 5 hari. Kelompok IV diberikan aquades selama 19 hari. Hari ke 27, femur mencit kiri diambil dan dijadikan sediaan parafin dengan pewarnaan hematoxylin-eosin, kemudian diamati di bawah mikroskop. Jumlah megakariosit terbanyak adalah pada Kelompok IV diikuti dengan II, III dan I. Berdasarkan uji Kruskal-Wallis, terdapat perbedaan bermakna (p<0,05) dilanjutkan uji Mann-Whitney yaitu terdapat perbedaan bermakna antara Kelompok I dengan II, III, dan IV, sedangkan perbandingan pada kelompok mencit normal dengan kelompok yang diberi ekstrak tidak terdapat perbedaan yang bermakna. Ekstrak jambu biji dapat meningkatkan jumlah megakariosit pada mencit yang mengalami trombositopenia dan tidak menyebabkan peningkatan jumlah megakariosit secara bermakna pada mencit normal.Kata kunci: Demam berdarah, ekstrak jambu biji, megakariosit, quinine